Prevention of breast cancer - the importance of screening tests - Elżbieta Cipora (Kazimierz Wielki University, 2017)
Abstract   Introduction. Breast cancer is the most common malignancy in women. It is one of the leading causes of death in the population of women in Poland. Purpose of the paper. Presentation of the desired behaviors and activities in the field of breast cancer prevention. Material and method. There has been carried out an analysis of the current scientific literature and reports available on the websites of the Ministry of Health concerning the recommendations and effects of breast cancer prevention among women in Poland. Results. A pro-health lifestyle conducive to reducing or eliminating the occurrence of disease factors is an important element of primary prevention of breast cancer. In secondary prevention, regular breast self-examination, medical examination and screening tests are important, with mammography being the most important factor in early diagnosis of breast cancer. Conclusions. Prevention of breast cancer should focus on the education of women of all ages on the need for regular breast self-examination, the use of medical examinations and, above all, participation in screening tests.